Meningkatkan Hasil Belajar PAK Melalui PBL Materi Gereja Fase F Di SMAN 1 Parenggean Kabupaten Kotawatingin Timur - Emanuel Tena; Hartutik Hartutik (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
This study aims to determine the increase in achievement targets from cognitive learning outcomes and cooperation through the PBL. The problems in class XI IPA are minimal cooperation, accustomed to using the lecture method and individualism. Student learning outcomes are below the achievement target set. Students' psychomotor skills are also less visible because students are rarely invited to do practicals. This type of research is classroom action research. The independent variable is cooperation with the PBL model and the dependent variable is student learning outcomes. The population was all class XI SMAN 1 Parenggean who were Catholics totaling 18 students and a sample of 14 students from class XI IPA. The data collection technique uses the Observation of the Mutual Cooperation Process and the Learning Outcomes Test. The data analysis technique uses the percentage formula. The results of this study are that there is an increase in cooperation through the PBL model in students of phase F class XI on the material meaning and nature of the church at SMA Negeri 1 Parenggean, which was carried out using the PBL learning model in cycle I and cycle II. There is an increase in the target of learning outcomes through the PBL model for students of phase F class XI on the material meaning and nature of the church at SMA Negeri 1 Parenggean.